A new Bambusoideae (Poaceae: Bambusoideae: Bambuseae: Guaduinae) from the Ituzaingó Formation (Pliocene-Pleistocene), Entre Ríos, Argentina - Brea, Mariana (2013)
This paper describes the anatomy and morphology of a new bamboo fossil, Guadua morronei sp. nov., from the Ituzaingó Formation in the Entre Ríos province, Argentina. The fossil culm is the second record of Bambusoideae in Pliocene-Pleistocene sediments from the Paraná Basin (Argentina) and the fifth record for South America. The culm or aerial vegetative axis fossil is woody with one solid node and one incomplete solid internode. The anatomy of the internode is characterized by an epidermal layer, subepidermal parenchyma and continuous sclerenchyma surrounding the first cycle of peripheral vascular bundles and cortical parenchyma. The vascular bundles consist of two large metaxylem vessels, protoxylem and phloem, and each vascular bundle is surrounded by sclerenchyma. The interfascicular parenchyma is composed of isodiametric cells. The anatomy of the node is characterized by xylem with only one metaxylem vessel. The results of the morphological and anatomical analyses of the fossil bamboo revealed a great affinity with the extant species of Guadua paraguayana. Guadua morronei sp. nov. is the first Guadua fossil species with a solid internode. The presence of this fossil bamboo culm in Pliocene-Pleistocene sediments may contribute to a better understanding of the evolutionary history and present diversity of these groups in the South American flora. © 2013 Elsevier B.V.